Proton density polarization of the doubly magic 40Ca core in 48Ca and EoS parameters. (25th January 2021) - Zenihiro, Juzo; Uesaka, Tomohiro; Sagawa, Hiroyuki; Yoshida, Satoshi
Abstract: The proton density polarization in ^48Ca by the eight neutrons added on the ^40Ca core is discussed. We adopt the proton density distributions determined by electron scattering and the neutron density distributions determined by proton elastic scattering in ^40Ca and ^48Ca . As a measure of the proton density polarization effect due to the neutrons, a ratio R of the peak values of the neutron density difference Δρ_n, peak between ^48Ca and ^40Ca to the proton one Δρ_p, peak is introduced and compared with the Hartree–Fock and Hartree calculations by non-relativistic and relativistic energy density functionals (EDFs), respectively. The value R shows clear correlations with the symmetry energy parameters J and L, but not with the isoscalar incompressibility K_∞ . The experimental value R can be reproduced by theoretical calculations using the EDFs with L=25 –50 MeV.